2005
DOI: 10.1111/j.1365-2559.2005.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma ex pleomorphic adenoma (CXPA): immunoprofile of the cells involved in carcinomatous progression

Abstract: Most CXPAs consist only of epithelial cells that have an immunoprofile comparable to ductal luminal cells of PA. These malignant luminal cells arise in the duct-like structures as intraductal carcinoma and probably only at this early stage of development should the lesion be considered as a non-invasive carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 19 publications
6
94
1
4
Order By: Relevance
“…The idea of several possible routes for malignant transformation in PA is supported by the fact that in their series, Weiler et al [5] noted that no intraductal carcinoma was detected in all five cases of myoepithelial carcinomatous transformation of PA. Similar findings have been reported by Altemani et al [29]. Whether this difference in malignant transformation is something that differs between ''carcinoma ex'' versus ''carcinosarcoma ex'' on a general scale needs to be studied in a larger series of cases.…”
Section: Discussionsupporting
confidence: 82%
“…The idea of several possible routes for malignant transformation in PA is supported by the fact that in their series, Weiler et al [5] noted that no intraductal carcinoma was detected in all five cases of myoepithelial carcinomatous transformation of PA. Similar findings have been reported by Altemani et al [29]. Whether this difference in malignant transformation is something that differs between ''carcinoma ex'' versus ''carcinosarcoma ex'' on a general scale needs to be studied in a larger series of cases.…”
Section: Discussionsupporting
confidence: 82%
“…However, for the purposes of our study the histological diagnosis of the malignant component was not important; it was the nature of the neoplastic cells that had undergone malignant transformation-epithelial cells only or epithelial and myoepithelial cells-confirmed morphologically and by a panel of antibodies 17 that was of interest. The tumours were also classified according to the extension of invasion related to the capsule of the previous Abbreviations: CXPA, carcinoma ex pleomorphic adenoma; PA, pleomorphic adenoma PA: intracapsular, minimally invasive (( 15 mm of invasion), and frankly invasive.…”
Section: Methodsmentioning
confidence: 99%
“…This neoplasm is defined as an epithelial malignant transformation within a primary (de novo) or recurrent PA, and often poses a diagnostic challenge to clinicians and cytopathologists, since its entity is difficult to diagnose pre-operatively [3,4]. In fact, Ca ex PA can be asymptomatic as most of them are not widely invasive on gross findings and often have similar clinical presentations as PA, however, patients with Ca ex PA have a poor prognosis due to infiltrative and destructive behavior, and thus, early and accurate diagnosis and aggressive surgical treatment (i.e., total or radical parotidectomy) can increase their survival rates [1-5]. Although any form of carcinoma can be observed and also be a mixture of subtypes, the malignant component of Ca ex PA is most often adenocarcinoma, not otherwise specified (NOS), and sometimes, may be salivary duct carcinoma (SDC), undifferentiated carcinoma, adenoid cystic carcinoma, or mucoepidermoid carcinoma [1,2,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Simpson RHW et al described that the majority of them arise de novo (as in the breast) probably from a pure in situ carcinoma [13]. Similar to Ca ex PA, aggressive clinical management in the early stage of SDC appears to be the only hope for good prognosis [5,6,8-11]. Thus, it is critical to establish an accurate preoperative diagnosis by fine-needle aspiration cytology, however, previous studies have indicated the difficulty of correct characterization of Ca ex PA and/or SDC due to sampling errors or inadequateness and misinterpretation [14,15].…”
Section: Introductionmentioning
confidence: 99%